DYNAMICS OF GEARS, FLEETS, CATCH AND FISHING SEASON OF SMALLSCALE TUNA FISHERIES IN LABUHAN LOMBOK, WEST NUSA TENGGARA - Bram Setyadji; Budi Nugraha (Research Center for Fisheries, 2015)
In Indonesia, about 80% of fishing activities are small-scale and play major role both economically and socially. Previous studies mostly concentrated in Java, while in eastern part of Indonesia the information still scarce and limited. The study was conducted from January to December 2013, describes in detail the gears, fleets and catch dynamics of the small-scale tuna fisheries operating based in Labuhan Lombok Coastal Fishing Port (PPP. Labuhan Lombok). Small-scale tuna fishery in Labuhan Lombok are characterized by the small boats less than 10 GT, operating both troll line and hand line simultaneously, targeting large tuna, skipjack tuna and small tuna. Fishing season starts from April to August and influence by southwest monsoon wind and the presence of middleman as the connector between fishers and the market are the main character of the small-scale fisheries business in this area.